Legal and Administrative Foundations of Police Activity in Social Order Protection and Public Security - A. V. Kuyanova; A. F. Yuritsin (Сибирское юридическое обозрение, 2014)
An attempt is made in the article to analyze the legal and administrative foundations of Russian police activity in the sphere of public order protection and public security.